Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-70028
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Radial Compressor Aeroacoustics Using CFD

Abstract: This paper focuses on the application of CFD to the prediction of radial compressor aeroacoustics. It concentrates mainly on automotive turbocharger operations in the low mass-flow range where blade leading-edge and tip separation reduce the compressor performance and induce transient flow behaviour. Whereas the blade-passing is tonal and at high frequency, usually beyond the human hearing range, transience in the flow are turbulence-dominated, broad-band in nature, and in magnitude a significant source of aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 0 publications
4
41
0
Order By: Relevance
“…They observed hysteretic behavior for Re C < 1 × 10 5 , which is assumed to be the cause for Reynolds-dependent behavior of the inner blade elements of the upstream turbine under design conditions. Another experimental set of S826 airfoil data was presented by Ostovan et al (2013) from Middle East Technical University (METU) in Turkey. They investigated lift and drag coefficients from Re C = 7.15 × 10 4 to Re C = 1.45 × 10 5 on a two-dimensional wing with a chord length of c L = 0.20 m. No hysteretic effects for low Reynolds numbers were found in this experiment.…”
Section: Model Turbines Rotor and Airfoil Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed hysteretic behavior for Re C < 1 × 10 5 , which is assumed to be the cause for Reynolds-dependent behavior of the inner blade elements of the upstream turbine under design conditions. Another experimental set of S826 airfoil data was presented by Ostovan et al (2013) from Middle East Technical University (METU) in Turkey. They investigated lift and drag coefficients from Re C = 7.15 × 10 4 to Re C = 1.45 × 10 5 on a two-dimensional wing with a chord length of c L = 0.20 m. No hysteretic effects for low Reynolds numbers were found in this experiment.…”
Section: Model Turbines Rotor and Airfoil Characteristicsmentioning
confidence: 99%
“…More information about the use of Star-CMM+ in rotating flows can be found in Mendonça et al (2012), for example.…”
Section: Cd-adapco (Cd-adapco)mentioning
confidence: 99%
“…The phenomenon may be related to the so-called tip clearance noise described by Raitor and Neise (2008), but Galindo et al (2015) found no influence of tip clearance ratio on whoosh noise. Simulations performed by Mendonça et al (2012) predicted a broadband noise at 70% of impeller rotation frequency, which corresponds to the whoosh noise frequency range. Mendonça et al ascribed the broadband feature to rotating stall, although their analysis was focused on the inducer flow behavior.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Numerical simulations are configured following the criteria used by Mendonça et al (2012). Detached eddy simulations with underlying k-ω SST turbulence model were performed using the rigid body motion approach.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation